A method for preparing highly uniform nano W-Ni pre-alloyed composite powder

Through complex precipitation method and medium-temperature-high temperature reduction technology, high-uniform nano W-Ni pre-alloy composite powder was prepared, which solved the problems of uneven distribution of nickel and sintering deformation, and achieved efficient densified sintering of W-Ni alloys.

CN115945694BActive Publication Date: 2025-03-25ZHONGKE FANYAN (HENAN) SUPERHARD MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211565063.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2025-03-25
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

In the existing W-Ni alloy powder preparation method, uneven nickel distribution leads to uneven tissue and sintering deformation, and the powder particle size is large or uneven.

Method used

By using the complex precipitation method, the direct co-precipitation reaction between nickel ions and tungstate ions is converted into a complex-precipitation equilibrium reaction between nickel ammonium ligand and metatungstate ions by introducing complexing agents to achieve atomic mixing and uniform precipitation of elements, followed by medium-temperature-high temperature reduction to prepare nanoscale W-Ni pre-alloy composite powder.

Benefits of technology

The obtained nano W-Ni pre-alloy composite powder has high uniformity and high sintering activity, and can achieve near-full densification of W-Ni alloy at lower temperatures, solving the problems of sintering deformation and uneven particle size.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115945694B_ABST
    Figure CN115945694B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a highly uniform nano W-Ni pre-alloyed composite powder, wherein the direct non-uniform co-precipitation reaction between nickel ions and tungstate ions is converted into a uniform precipitation reaction between nickel-ammonia ligands and metatungstate ions by introducing a complexing agent ammonia water, so that the precipitation product obtains a spherical feature and tends to be uniform in morphology, composition and particle size distribution, and then the precipitate is dried, calcined and reduced to obtain a nano-scale W-Ni pre-alloyed composite powder. The present invention adopts a method for preparing a highly uniform nano W-Ni pre-alloyed composite powder using the above method, and the present invention can quickly obtain a nano-scale composite powder with completely uniform mixing between elements and a high degree of pre-alloying, and can realize nearly full densification of W-Ni alloy sintering at a relatively low temperature, and the preparation method is simple and fast, and can be used in industrial production in batches.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano powder preparation, in particular to a method for preparing highly uniform nano W-Ni pre-alloyed composite powder. Background Art

[0002] W-Ni alloy has the characteristics of high melting point, high hardness, high strength, wear resistance, corrosion resistance and radiation resistance, and has very important applications in the fields of nuclear energy, medical treatment, etc. Tungsten-nickel alloy is usually prepared by powder metallurgy. The uniformity and particle size characteristics of the powder have a very important influence on the uniformity of the organization and sintering performance of the alloy, especially for W-Ni alloy with high Ni content (such as 75~85W-Ni). If the nickel distribution is uneven, it is very easy to have uneven organization and abnormal growth of local grains. In addition, when high-temperature liquid phase sintering is used, due to the large amount of liquid phase, sintering deformation is very likely to occur.

[0003] At present, the main preparation methods of W-Ni powder include mechanical alloying, atomization (such as plasma rotating electrode, etc.), co-precipitation, etc. Among them, mechanical alloying can realize the pre-alloying of W-Ni powder and the grains reach the nanometer level, but the powder is easy to be flaky, the formability is poor, and impurities are easily introduced. Although the plasma rotating electrode atomization method can realize the alloying of W-Ni powder, the particle size of the powder is large (10 to 50 microns), and due to the large difference in the melting points of W and Ni, the powder particles are prone to component segregation. The direct co-precipitation method obtains a uniform composite precursor through chemical precipitation, but it is a non-uniform precipitation under actual reaction conditions, and the obtained powder still has problems of uneven morphology, particle size and component distribution.

[0004] To this end, the present invention uses a complex precipitation method to solve the problem of homogenization of precipitation reaction on the one hand, and at the same time achieves atomic-level mixing of various elements, and adopts medium-temperature and high-temperature reduction to prepare nano W-Ni pre-alloyed composite powder with a higher degree of pre-alloying. By utilizing its nano and pre-alloyed high sintering activity, the W-Ni alloy is nearly fully densified by solid phase sintering at 1350-1420°C, and the problem of alloy sintering deformation is solved. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing highly uniform nano W-Ni pre-alloyed composite powder, so as to solve the problem of uneven morphology, particle size and component distribution of the alloy composite powder prepared by the above preparation method. On the one hand, the present invention takes advantage of the precipitation method to achieve atomic-level mixing of various elements in the product in one step, and further makes the precipitation process smooth, uniform and controllable, thereby obtaining nano-scale precipitated particles with a particle size. The precipitated particles are reduced at medium temperature to high temperature to obtain nano W-Ni pre-alloyed composite powder.

[0006] To achieve the above-mentioned purpose, the present invention provides a method for preparing highly uniform nano W-Ni pre-alloyed composite powder, in which a complexing agent is introduced to convert the direct coprecipitation reaction between nickel ions and tungstate ions into a complex-precipitation equilibrium reaction between nickel ammonia ligands and metatungstate ions, thereby converting non-uniform precipitation into uniform precipitation, and the precipitate is dried, calcined and reduced to obtain a nano-scale W-Ni pre-alloyed composite powder.

[0007] Preferably, the method comprises the following steps:

[0008] Step S1, mother liquor preparation: using nickel nitrate as nickel source, ammonia water as complexing agent, ammonium metatungstate solution as tungsten source and precipitant, PEG400 as dispersant, first prepare a stable nickel-ammonia complex system, then add dispersant and precipitant in sequence, and before adding precipitant, adjust the pH value of mother liquor with dilute nitric acid;

[0009] Step S2, water bath reaction: the water bath reaction is carried out in an open thermostatic device with stirring conditions, the water bath temperature is 80-85° C., and the water bath time is 30-90 min;

[0010] Step S3, drying: filtering the mother liquid after the reaction and drying it to obtain a precipitated product powder;

[0011] Step S4, calcining: calcining the precipitated product in air to obtain a composite oxide powder;

[0012] Step S5, reduction: reducing the composite oxide powder in a hydrogen atmosphere to obtain nano W-Ni alloy composite powder.

[0013] Preferably, the pH value of the mother liquor in step S1 needs to be calculated and determined according to the reaction conditions, and the appropriate reaction pH value range should meet the following requirements:

[0014] The lowest pH value at which the complex does not produce an acid effect in the mother liquor is the lower limit;

[0015] The upper limit is the maximum pH value at which the free nickel ions preferentially combine with the tungstate ions in thermodynamics and no hydroxide precipitation is generated. The choice of pH value determines the composition of the product alloy. The principle is that according to the needs of the composition, the composition of the hydrolysis product of the metatungstate ions is controlled by adjusting the pH value, and the concentration and addition amount of the precipitant are adjusted accordingly to obtain a precipitation product with a specific stoichiometric ratio.

[0016] Preferably, in step S1, according to the molar concentration in the mother liquor, the nickel nitrate in the mother liquor is 0.5-1.5 mol / L, the NH3 concentration is 1.0-5.0 mol / L, the ammonium metatungstate is 0.05-0.20 mol / L, the dispersant is 3%-5%, and the rest is deionized water. When the mother liquor is prepared, the nickel source and the complexing agent are first fully mixed, and then the dispersant and the precipitant are added in sequence. Before adding the precipitant, the pH value of the mother liquor needs to be adjusted to 7-12 with dilute nitric acid.

[0017] Preferably, the drying of the precipitate in step S3 is carried out in a vacuum drying oven or an oven, with a drying temperature of 130 to 140° C. and a drying time of 60 to 90 min.

[0018] Preferably, the calcination temperature of the precipitated product in step S4 is 450-550° C., and the calcination time is 60-120 min.

[0019] Preferably, in step S5, the composite oxide is subjected to medium-temperature-high-temperature reduction in a hydrogen atmosphere, wherein the medium-temperature reduction temperature is 450-500° C. and the insulation time is 60-120 min; the high-temperature reduction temperature is 700-750° C. and the reduction time is 60-120 min.

[0020] Preferably, the reduction equipment used is a tubular hydrogen reduction furnace, the heating element is a molybdenum wire, the hydrogen dew point is -60°C, the hydrogen flow rate is 60-100 mL / s, and the layer material thickness is ≤50 mm.

[0021] The method of the present invention is used to prepare W-Ni pre-alloyed composite powder. The precipitation process is uniform and slow. The obtained precipitation product has high sphericity and uniform particle size distribution. W and Ni in the particles are uniformly mixed at the atomic level. The particle size of the primary particles reaches the nanometer level and has the characteristics of uniform precipitation. The alloy composition can be controlled by adjusting the pH value of the mother solution. The operation is simple and easy to carry out industrial production.

[0022] The method for preparing nano W-Ni pre-alloyed composite powder provided by the present invention solves the problems of uneven morphology, particle size and component distribution of the direct co-precipitation method, and realizes uniform component distribution and pre-alloying of W and Ni elements at the atomic level; compared with the powder prepared by mechanical alloying and atomization, the particle size is finer and the sintering activity is high, and the W-Ni alloy can be nearly fully densified at 1350-1420° C. in solid phase sintering, and the grain structure is uniform and fine, and the problem of easy deformation of alloys with high Ni content (such as W-25Ni, with Ni volume fraction exceeding 40%) during sintering is solved.

[0023] Therefore, the present invention adopts a method for preparing a highly uniform nano W-Ni pre-alloyed composite powder of the above structure, which has the following beneficial effects:

[0024] 1. Compared with mechanical alloying and atomization methods, the W-Ni pre-alloyed composite powder prepared by the method of the present invention has completely uniform mixing of elements in the powder, a high degree of pre-alloying, a nano-scale particle size, and high sintering activity.

[0025] 2. Compared with direct co-precipitation, the introduction of the complex system solves the problem of non-uniform precipitation in the precipitation reaction, so that the obtained alloy powder has spherical characteristics and good uniformity in morphology, composition and particle size distribution.

[0026] 3. The W and Ni components in the W-Ni pre-alloyed composite powder of the present invention can be adjusted as needed, and the preparation method is simple and fast. The alloy composition can be controlled by reaction conditions and can be used in industrial production in batches.

[0027] 4. The W-Ni pre-alloyed composite powder of the present invention can be nearly fully densified by solid phase sintering at 1350-1420°C, and the grain structure is uniform and fine, which solves the deformation problem of high-density W-Ni alloy during liquid phase sintering, and is particularly effective for alloys with high Ni content.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a TEM microscopic morphology image of 85W-Ni powder prepared in Example 1 of the powder preparation method provided by the present invention;

[0030] Figure 2 TEM electron diffraction analysis results of 85W-Ni powder prepared in Example 1 of the powder preparation method provided by the present invention;

[0031] Figure 3 This is a TEM microscopic morphology image of 80W-Ni powder prepared in Example 2 of the powder preparation method provided by the present invention;

[0032] Figure 4 This is a TEM microscopic morphology image of 75W-Ni powder prepared in Example 3 of the powder preparation method provided by the present invention;

[0033] Figure 5 The microstructures of the 75W-Ni powder prepared in Example 3 of the powder preparation method provided by the present invention after sintering at 1350° C. and 1400° C. respectively. DETAILED DESCRIPTION

[0034] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.

[0035] Example 1: 85W-Ni pre-alloyed powder

[0036] Add excess ammonia to a 1 mol / L Ni(NO3)2 solution to obtain a stable [Ni(NH3)4] 2+ The system solution is then added with 5% (wt.%) of PEG400 dispersant, and the pH value of the solution is adjusted to 7-8 with dilute nitric acid, and an excess of 0.15 mol / L ammonium metatungstate solution is added thereto while stirring, and the reaction mother liquor is obtained after being stirred evenly. The mother liquor is placed in a water bath at 80°C for 90 minutes under stirring conditions, and the precipitate is dried at 130°C for 90 minutes and then calcined at 450°C for 120 minutes. The calcined powder is reduced under hydrogen, first at 450°C for 120 minutes, and finally at 750°C for 60 minutes, and 85W-Ni pre-alloyed composite powder is obtained after reduction.

[0037] The TEM morphology of the 85W-Ni alloy powder prepared in this example is as follows: Figure 1 The electron diffraction analysis results of primary particles are shown in Figure 2 As shown, it can be seen that W and Ni are alloyed, the primary particles of the powder are polygonal, the average particle size of a single particle is between 80-100nm, reaching the nanometer level, and the particles contain diffraction patterns of W crystals and Ni crystals at the same time, which has the characteristics of alloying. It is a nanometer-level W-Ni pre-alloyed composite powder.

[0038] Example 2: 80W-Ni pre-alloyed powder

[0039] Add excess ammonia to 1 mol / L Ni(NO3)2 solution to obtain a stable [Ni(NH3)4] 2+ The system solution is then added with 3% (wt.%) of PEG400 dispersant, and the pH value of the solution is adjusted to 8-9 with dilute nitric acid, and an excess of 0.1 mol / L ammonium metatungstate solution is added thereto while stirring, and the reaction mother solution is obtained after being stirred evenly. The mother solution is placed in a water bath at 80°C for 90min under stirring conditions, and the precipitate is dried at 140°C for 60min and then calcined at 500°C for 90min. The calcined powder is reduced under hydrogen, first at 500°C for 80min, and finally at 720°C for 90min, and 85W-Ni pre-alloyed composite powder is obtained after reduction.

[0040] The TEM morphology of the 80W-Ni alloy powder prepared in this example is as follows: Figure 3 As shown, the specific surface area is 9.96m 2 / kg.

[0041] Example 3: Preparation of 75W-Ni alloy powder by complex precipitation method

[0042] Add excess ammonia to 1 mol / L Ni(NO3)2 solution to obtain a stable [Ni(NH3)4] 2+ The system solution is then added with 3% (wt.%) of PEG400 dispersant, and the pH value of the solution is adjusted to 9-10 with dilute nitric acid, and an excess of 0.08 mol / L ammonium metatungstate solution is added thereto while stirring, and the reaction mother solution is obtained after being stirred evenly. The mother solution is placed in a water bath at 80°C for 90min under stirring conditions, and the precipitate is dried at 140°C for 60min and then calcined at 550°C for 60min. The calcined powder is reduced under hydrogen, first at 550°C for 60min, and finally at 700°C for 90min, and the 75W-Ni pre-alloyed composite powder is obtained after reduction.

[0043] The TEM morphology of the 75W-Ni pre-alloyed powder prepared in this example is as follows: Figure 4 As shown in the figure, it can be seen that when the Ni content is high, the surface of the W particles is evenly coated with Ni, and the specific surface area is 10.99m 2 / kg. And after sintering the 75W-Ni pre-alloyed powder at 1350℃ and 1400℃, the grains are fine and the microstructure is evenly distributed (such as Figure 5 As shown in the figure, it can be seen that the structure of the alloy is very uniform and the W grain size is small.

[0044] Therefore, the present invention adopts a method for preparing a highly uniform nano WNi pre-alloyed composite powder with the above structure, which can quickly obtain a nano-scale composite powder with a completely uniform mixing of elements and a high degree of pre-alloying, and can achieve nearly full densification of W-Ni alloy by sintering at a lower temperature. The preparation method is simple and fast and can be used in industrial production in batches.

[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing highly uniform nano W-Ni pre-alloyed composite powder, characterized in that: By introducing a complexing agent ammonia water, the direct coprecipitation reaction between nickel ions and tungstate ions is converted into a complexation-precipitation equilibrium reaction between nickel-ammonia ligands and metatungstate ions, and the non-uniform precipitation is changed into uniform precipitation. After the precipitate is dried, calcined and reduced, a nano-scale W-Ni pre-alloyed composite powder is obtained. The specific steps include: Add excess ammonia to a 1 mol / L Ni(NO3)2 solution to obtain a stable [Ni(NH3)4] 2+ The system solution is then added with 3wt.% of PEG400 dispersant, the pH value of the solution is adjusted to 9-10 with dilute nitric acid, and an excess of 0.08mol / L ammonium metatungstate solution is added thereto while stirring, and the reaction mother solution is obtained after stirring evenly; The mother liquor was placed in a water bath at 80°C for reaction under stirring conditions for 90 minutes, and the precipitate was dried at 140°C for 60 minutes, and then calcined at 550°C for 60 minutes. The calcined powder was reduced under hydrogen, first at 550°C for 60 minutes and finally at 700°C for 90 minutes. After reduction, a pre-alloyed composite powder was obtained, and the pre-alloyed composite powder was 75W-Ni; the surface of the W particles in the pre-alloyed composite powder was uniformly coated with Ni.

2. The method for preparing a highly uniform nano W-Ni pre-alloyed composite powder according to claim 1, characterized in that: The reduction equipment used is a tubular hydrogen reduction furnace, the heating element is a molybdenum wire, the hydrogen dew point is -60°C, the hydrogen flow rate is 60-100mL / s, and the layer material thickness is ≤50mm.